Yours for justice, Ida B. Wells : the daring life of crusading journalist - Dray, Philip (Peachtree, 2021)
Uses bright illustrations and an engaging text to describe the life of African-American civil rights worker Ida Barnett Wells, focusing on her challenge to end lynching in America. Ida left a legacy of activism for freedom and equality that would empower the Civil Rights Movement into the 1950s and 1960s.